Rivers and waterways in the Roman world
1 online resource (xvi, 255 pages)
Keywords: "Taking a broad geographical, temporal, and cross-disciplinary approach, this volume explores new and innovative research which focuses on waterways and rivers (including estuaries, lagoons, and canals) from across the Roman Empire. Rivers and Waterways in the Roman World brings together cross-disciplinary chapters focussing on theoretical approaches, new digital and scientific methods and analytical techniques, and related surveying and excavation case studies to examine the Romans extensive use of rivers and inland waterways around the Empire. Roman seafaring is well studied but this book expands our knowledge of Roman transport, communication and trade networks inland. The book highlights the challenges of archaeological work in the dynamic environments of rivers and waterways and showcases the use of new methodologies, including the increasing availability and accessibility of digital technologies that have led to a growth in the development and application of new archaeological and analytical techniques, as well as the discovery of new archaeological sites, many of which were previously inaccessible. This book is for archaeologists, historians, and classicists with an interest in the history and archaeology of the Roman Empire"--